Life Cycle Assessment of Biofuel Production from Sugarcane Bagasse - Nasri Nurul Farhana; Mohd Hanafiah Marlia; Harun Siti Norliyana; Chong Jing Wen; Hassan Faez M. (E3S Web of Conferences)
Fossil fuels dominate global energy supply, accounting for over 80% of total consumption. Biofuels derived from renewable resources emerge as a promising alternative to reduce dependence on fossil fuels and mitigate greenhouse gas (GHG) emissions. This study evaluated the environmental impact and hotspots of biofuel production from sugarcane bagasse using a Life Cycle Assessment (LCA) approach. The LCA was performed using SimaPro version 9.0 software, utilizing the ReCiPe 2016 methodology in a ’cradle-to-gate’ framework. The functional unit in this study was 252 kg of bioethanol produced from 1 ton of sugarcane bagasse. The findings revealed that biofuel production from sugarcane significantly impacts terrestrial ecotoxicity (10.44 kg 1,4-DCB), human non-carcinogenic toxicity (2.61 kg 1,4-DCB), and global warming (2.60 kg CO2 eq). The characterization factors for human health damage, ecosystem damage, and resource depletion were 3.68E-04 DALY, 3.04E-05 species.year, and 6.91E06 USD2013, respectively. These results offered valuable insights into the environmental footprint of biofuel production from sugarcane bagasse, providing essential information for policymakers and industry stakeholders to develop more sustainable energy strategies in line with the Sustainable Development Goals (SDGs).